APONTAMENTOS SOBRE A EFETIVIDADE DA USUCAPIÃO CONSTITUCIONAL URBANO - HEIDEMANN, MARISTELA; PROBST, CARLOS G.; OLIVEIRA, CLAIRTON R. D.; CARVALHO, TAÍS K. M. D.; MACHADO, ANDRÉIA C.; ZENI, BRUNA S.; BURKHARDT, CAROLINA M.; CHAGAS, CLÁUDIA M. P.; PFEIFER, DAGMAR D. L.; FILIPIN, ENIO; MACHADO, EVERTON E.; VIANNA, MINÉIA; et al. (Salão do Conhecimento, 2013)
Resumo